2008
DOI: 10.1177/0095798408314140
|View full text |Cite
|
Sign up to set email alerts
|

Acting “Tough” in a “Tough” World: An Examination of Fear Among Urban African American Adolescents

Abstract: African American adolescents (132 males and 128 females; age M = 14.8 years, SD = 0.92) enrolled in an urban community social skills development program participated in a study assessing the relationship among perceptions of family and community social support, fear of calamitous events, depression, and anger expression. Expressing fear of calamitous events that were considered harmful but not necessarily lethal was related to increased depression, whereas expressing fear of lethal calamitous events was relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 36 publications
6
32
0
Order By: Relevance
“…As a main effect, social support was negatively associated with depressive symptoms. This finding is consistent with previous literature suggesting the positive influence of social support on depressive symptoms (Gaylord-Harden et al, 2007; Hall, Cassidy, & Stevenson, 2008; Zimmerman et al, 2000). Interestingly, in the Hall et al (2008) study, this main effect was only found for girls.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a main effect, social support was negatively associated with depressive symptoms. This finding is consistent with previous literature suggesting the positive influence of social support on depressive symptoms (Gaylord-Harden et al, 2007; Hall, Cassidy, & Stevenson, 2008; Zimmerman et al, 2000). Interestingly, in the Hall et al (2008) study, this main effect was only found for girls.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous literature suggesting the positive influence of social support on depressive symptoms (Gaylord-Harden et al, 2007; Hall, Cassidy, & Stevenson, 2008; Zimmerman et al, 2000). Interestingly, in the Hall et al (2008) study, this main effect was only found for girls. As an interactive effect, regression coefficients indicated that the negative relationship between mental health stigma and depressive symptoms increased with every increase in level of social support.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, African American adolescent boys experience the highest fatal and non-fatal drowning rates, but they have lower levels of fear for drowning/being injured while swimming than African American girls. This finding matches research that found that African American adolescent males adopt a "tough guy" attitude in order to avoid depression and anxiety that typically emerges when living in a dangerous environment (Hall, Cassidy, & Stevenson, 2008). This hard exterior persona and lower levels of fear may explain why African American adolescent boys drown at such high rates.…”
Section: Discussionsupporting
confidence: 84%
“…These results were expected, as there have been several studies showing that weaker social support is associated with greater depression and psychological distress within African American populations (Ceballo & McLoyd, 2002; McKnight-Eily et al, 2009; Thompson et al, 2000). For instance, kinship support has been found to be negatively correlated with adolescent depression symptoms and behavior problems in single-parent households (Hall et al, 2008; Taylor et al, 1993). Also, in a study with both African American and Caucasian mothers with depression, lower satisfaction with support networks was associated with higher rates of internalizing disorders in their children (McCarty et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Construct validity of this measure is demonstrated by positive correlations with measures of family routines and informal kinship support (Jones, 2007; Taylor, Seaton, & Dominquez, 2008). The Kinship Support Scale has adequate internal consistency (0.72 - 0.86) for African American youth (Hall, Cassidy, & Stevenson, 2008; Jones, 2007; Kenny, Blustein, Chaves, Grossman, Gallagher, 2003; Taylor et al, 1993). Strong internal consistency (α =.88) has been found in a sample of low-income African American mothers (Taylor & Roberts, 1995).…”
Section: Methodsmentioning
confidence: 99%